2012
DOI: 10.1371/journal.pone.0050361
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsolateral Periaqueductal Gray and Its Role in Mediating Fear Learning to Life Threatening Events

Abstract: The dorsolateral column of the periaqueductal gray (dlPAG) integrates aversive emotional experiences and represents an important site responding to life threatening situations, such as hypoxia, cardiac pain and predator threats. Previous studies have shown that the dorsal PAG also supports fear learning; and we have currently explored how the dlPAG influences associative learning. We have first shown that N-methyl-D-aspartate (NMDA) 100 pmol injection in the dlPAG works as a valuable unconditioned stimulus (US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 58 publications
3
53
1
1
Order By: Relevance
“…1, the dorsal PAG, in particular its dorsolateral part, which presents a distinct activation during exposure to an ambiguous predatory threat (Cezario et al, 2008;Dielenberg et al, 2001), provides dense projections to the anterior hypothalamic nucleus (AHN) and adjacent parts of the subfornical region of the lateral hypothalamic area (LHAsf; Kincheski et al, 2012), both of which up-regulate Fos expression in response to predator threat (Cezario et al, 2008). Both the AHN and the LHAsf represent the main ascending targets of the dorsolateral PAG (Kincheski et al, 2012) and provide a rather massive projection to the rostral part of the lateral septum, particularly to the dorsolateral zone (LSr.dl; Fig. 1) Risold et al, 1994).…”
Section: Pag and Anxious Responsementioning
confidence: 99%
See 1 more Smart Citation
“…1, the dorsal PAG, in particular its dorsolateral part, which presents a distinct activation during exposure to an ambiguous predatory threat (Cezario et al, 2008;Dielenberg et al, 2001), provides dense projections to the anterior hypothalamic nucleus (AHN) and adjacent parts of the subfornical region of the lateral hypothalamic area (LHAsf; Kincheski et al, 2012), both of which up-regulate Fos expression in response to predator threat (Cezario et al, 2008). Both the AHN and the LHAsf represent the main ascending targets of the dorsolateral PAG (Kincheski et al, 2012) and provide a rather massive projection to the rostral part of the lateral septum, particularly to the dorsolateral zone (LSr.dl; Fig. 1) Risold et al, 1994).…”
Section: Pag and Anxious Responsementioning
confidence: 99%
“…In line with this view, in experiments using an olfactory fear conditioning paradigm associating a neutral odor as the CS and chemical stimulation of the dorsal premammillary nucleus (to mimic live predator threat exposure) as a US, it has been shown that the integrity of the dorsal PAG is necessary to support fear learning (Pavesi et al, 2011). Moreover, a number of studies using classical fear conditioning to sound-, lightor odor-conditioned stimuli (CS) have shown that electrical, chemical or optogenetic stimulation of the dorsal PAG may be used as a useful US to support associative learning (Deng et al, 2016;Di Scala et al, 1987;Di Scala and Sandner, 1989;Kincheski et al, 2012;Kim et al, 2013). Therefore, the dorsal PAG may be viewed as an important site to respond to life threatening events and, at the same time, to influence fear learning.…”
Section: Pag and Fear Learningmentioning
confidence: 99%
“…Pharmacological activation of PAGd is sufficient to induce defensive responses to the context where the stimulation occurred (Kincheski et al 2012). The mnemonic effects of PAG stimulation may be mediated by PAG projections to PMD, as well as by direct projections to thalamic nuclei including intralaminar, laterodorsal, reuniens, suprageniculate, and subparafascicular thalamic nuclei (Kincheski et al 2012).…”
Section: Environment-appropriate Fear Responsesmentioning
confidence: 99%
“…Pharmacological activation of PAGd is sufficient to induce defensive responses to the context where the stimulation occurred (Kincheski et al 2012). The mnemonic effects of PAG stimulation may be mediated by PAG projections to PMD, as well as by direct projections to thalamic nuclei including intralaminar, laterodorsal, reuniens, suprageniculate, and subparafascicular thalamic nuclei (Kincheski et al 2012). However, pharmacogenetic inhibition of dorsal PAG does not impair predator learning despite reducing acute fear responses (Silva et al 2016), implying that at least for VMH, the PAG does not mediate the mnemonic effects of MHDS stimulation, but by a so far unknown route.…”
Section: Environment-appropriate Fear Responsesmentioning
confidence: 99%
“…Recent studies have indicated the importance of RE for cognitive processes, such as behavioural flexibility, strategy shifting, inhibitory response control, associative learning, memory consolidation, working memory, fear memory, memory generalization, goal-directed navigation, and executive behaviours (Dollemanvan der Weel et al 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Kincheski et al 2012;Loureiro et al 2012;Cholvin et al 2013;Hallock et al 2013;Prasad et al 2013;Varela et al 2013;Wheeler et al 2013;Xu and Sűdhof 2013;Duan et al 2015;Griffin 2015;Ito et al 2015;Layfield et al 2015;Anderson et al 2015;Prasad et al 2016). This variety of memory-related behaviours has also been associated with the interplay between the medial prefrontal cortex (mPFC) and the hippocampus (Jin and Maren 2015).…”
Section: Introductionmentioning
confidence: 99%